Use of geometry and featural cues in landmark configurations to reorient DCD children to the VR space: A route-learning study. - Basdekidou, Chrysanthi; Styliadis, Athanasios; Argyriadis, Alexandros; Dimen, Levente (Revista de Investigación e Innovación en Ciencias de la Salud (RIICS), 2024)
Background. Working memory-based spatial cognition has attracted the attention of the scientific community in navigation and reorientation projects. The dominant approach considers that spontaneous spatial navigation behavior is based merely on environmental geometry (built and natural environmental objects). In this domain, DCD (Developmental Coordination Disorder) motor skill orientation problems have been frequently associated with poor visuospatial cognition, while immersive VR environments encourage more repetition, allowing for faster motor skill development and recovery. Objective. This pilot study tested the functionality of an immersive VR environment with environmental geometry (rectangular arena rich in symmetry) and featural landmark cues (striped wall, flora) as a route-learning tool for children with motor skill disorders. Methods. Forty DCD children aged 5 to 8 years (20 boys and 20 girls); five (5) 3D reality modeling setups with orthogonality, symmetry, and striped walls as design parameters; and trial walk-through coordination exercises using a predefined visual pathway with different motor control conditions (daylight, darkness). Participants' path completion rate, path completion time, and walk-through satisfaction were recorded as route-learning performance variables and analyzed statistically. Results/findings. DCD children's spatial orientation was statistically shown to be more stable and robust (in path completion rates, termination time, and walk-through level of satisfaction) in a virtual 3D environment rich in orthogonality, symmetry, and featural cues as landmarks. In this compound environmental geometry setup, training functionality and immersive learning performance enjoyed an 8.16% better path completion rate, a 12.37% reduction in path completion time, and 32.10% more walk-through satisfaction than reality modeling setups poor in geometry and landmarks. The effectiveness and robustness were validated statistically. Conclusion. Children with motor skill difficulties train and learn better in virtual 3D environments that are rich in orthogonality, symmetry, and featural landmark cues.